Genome editing for sustainable agriculture in Peru: advances, potential applications and regulation - Mestanza, Marilu; Hernández-Amasifuen, Angel David; Pineda-Lázaro, Alexandra Jherina; Eriksson, Dennis; Guerrero-Abad, Juan Carlos (Frontiers in Genome Editing, 2025)
Peruvian agriculture is characterize by crops such as potato, maize, rice, asparagus, mango, banana, avocado, cassava, onion, oil palm, chili, papikra, blueberry, coffee, cacao, grapes, quinoa, olive, citrus and others. All of them have challenges in production in their specific agroecosystems under stress due to pests, diseases, salinity, drought, cold among others. Gene editing through CRISPR/Cas is a key tool for addressing critical challenges in agriculture by improving resilience to biotic and abiotic stress, increasing yield and enhancing the nutritional value of the crops. This approach allows precise mutation on site-specific gene at the DNA level, obtaining desirable traits when its function is altered. The CRISPR/Cas system could be used as a transgene-free genome editing tool when the ribonucleoprotein (RNP) acts as a carrier to delivered the CRISPR/Cas components into the plant cell protoplasts, or when the tRNA-like sequence (TLS) motifs are fused to single-guide RNA (sgRNA) and Cas mRNA sequence and expressed in transgenic plants rootstock to produce “mobile” CRISPR/Cas components to upper tissue (scion). Those innovations could be a potential approach to strengthen the Peruvian agriculture, food security and gricultural economy, especially in the tropical, Andean and coastal regions. This review article examines the advances and strategies of gene editing, focusing on transgene-free methodologies that could be adopted for research, development and use, and also identifies potential applications in key crops for Peru and analyzes their impact in the productivity and reduction of agrochemicals dependence. Finally, this review highlights the need to establish regulatory policies that strengthen the use of biotechnological precise innovations, ensuring the conservation and valorization of agrobiodiversity for the benefit of Peruvian farmers.